BREAST SARCOMA (World Bulletin of Public Health, 2025)
Breast sarcoma is a rare and aggressive malignancy arising from the mesenchymal tissues of the breast. Unlike the more common epithelial breast carcinomas, sarcomas demonstrate distinct biological behavior, clinical presentation, and treatment requirements. Early diagnosis and accurate histopathological classification are essential for effective management. This review provides an overview of the epidemiology, clinical features, histological subtypes, and therapeutic approaches for breast sarcoma.
Keywords: Breast sarcoma; mesenchymal tumor; histopathology; treatment